Research of the Brake Noise Prediction of Wet Brake based on Complex Mode Finite Element Method - Luo Tianhong; Cui Tingqiong; Lu Shiqiu; Li Deshan (Jixie chuandong)
Aiming at the problem of the vibration noise in the braking process of wet multi- disc brake,the damping and stiffness between the brake disc friction plate and the steel disk are introduced based on the consideration of the small relative displacement of the brake disc and the friction lining due to time delay,otherwise,the contact friction relations of braking component and their effect also take into consideration. By using the nonlinear contact kinematics,the analysis model of the wet brake noise is proposed and the accuracy of this model is verified by using the complex modal finite element simulation analysis. The results show that this kind of model can predict the brake noise more accurately during braking,and the research has vital importance to practical engineering.